PERBANKAN SYARIAH DAN PEMBERDAYAAN UMAT - Florentius Nugro Hardianto (Bina Ekonomi, 2009)
Syariah Banking System aimed to support national  development in improving  justice, togetherness, and spreading of people's welfare. There are three characteristics of Syariah Banking System which are unique and synergize of each other i.e. theologist, locality, and economic democration. Those three characteristics will be the spirit of Syariah Banking System in empowerment of people  in particular, moslems. In practice, Syariah Banking System has a number of function either in financial mediation, or in practicing its social function towards society. Even though currently Syariah Banking System  experienced  significant progress, efforts are still needed in encouraging  the government to improve political will in development  of Syariah Banking System,  increase capital of Syariah Banking System, and to strengthen socialization of Syariah Banking System with broader scopes.